Per, Me, ng PERBEDAAN ANGKA KARIES PADA ANAK YANG MENGKONSUMSI ASI EKSKLUSIF DENGAN SUSU FORMULA PADA UMUR 3-4 TAHUN DI PAUD DAN TK A TERPADU NEGERI PEMBINA BANJARMASIN TIMUR: - Nur Izzatil Hasanah; Naning Kisworo Utami; Rasuna Ulfah; Danan (JURNAL TERAPIS GIGI DAN MULUT, 2026)
Based on 2018 Indonesia Basic Health Research, dental problems such as decay, cavities and toothache are still high in Indonesia, especially in children, with a prevalence reaching 45.3%. This condition has an impact on the child's chewing function, digestion and growth. Dental caries in children aged 3-4 years is also very high, namely 82%, indicating low awareness of the importance of dental health from an early age. This study aims to determine the difference in caries rates in childrenwho consume exclusive breast milk and formula milk in Early Childhood Education and Kindergarten A Terpadu Negeri Pembina East Banjarmasin. Types of research analytical quantitative with a plan cross sectional. Sampling used total sampling with a sample size of 52 respondents. Data analysis using tests Independent Sampel T-test. The research results showed that the average caries of children who consumed exclusive breast milk was 4,77, while the average caries of children whoconsumed formula milk was 6,16. Based on test results Independent Sampel T-test The ???? (0,015) with ???? (0,05) so that ???? < ???? means that Ho is rejected. Ha is accepted. The conclusion of this research is that there is a difference in caries rates in children who consume exclusive breast milk and formula milk at the age of 3-4 years in Early Childhood Education and Kindergarten A Terpadu Negeri Pembina East Banjarmasin. Parents are advised to know more about the benefits of exclusive breastfeeding which is very good for dental health rather than giving formula milk.